EphA4 Negatively Regulates Myelination by Inhibiting Schwann Cell Differentiation in the Peripheral Nervous System - Chen, Ruyue; Yang, Xiaoming; Zhang, Bin; Wang, Shengran; Bao, Shuangxi; Gu, Yun; Li, Shiying (Frontiers in Neuroscience, 2019)
Myelin plays a crucial role in axon function recovery following nerve damage, and the interaction between Schwann cells (SCs) and regenerating axons profoundly affects myelin formation. Eph receptor A4 (EphA4), a member of the Eph tyrosine kinase receptor family, regulates cell-cell interactions via its ligand ephrins. However, our current knowledge on how EphA4 regulates the formation of myelin sheaths remains limited. In order to explore the roles of EphA4 in myelination in the peripheral nervous system, we used a combination of 1) a co-culture model of dorsal root ganglion (DRG) explants and SCs, 2) a SC differentiation model induced by db-cAMP, and 3) a regeneration model of crushed sciatic nerves in rats. Our results demonstrated that EphA4 inhibited myelination by inhibiting SC differentiation and facilitating SC proliferation in vitro. The in vivo experiments revealed that EphA4 expression in SCs is upregulated following nerve crush injury and then downregulated during remyelination. Moreover, silencing of EphA4 by siRNA or overexpression of EphA4 by genetic manipulation can accelerate or slow down nerve remyelination in crushed sciatic nerves. Taken together, our results suggest that EphA4 may negatively regulate myelination by abrogating SC differentiation.